Getting It Right: What Needs to be Done to Ensure First Nations’ Participation and Benefit from Large-Scale Renewable Energy Developments on Country? - Quail, K; Green, D; O’Faircheallaigh, C (Routledge, 2023)
Australia has excellent solar and wind resources and is close enough to Asian markets to enable the export of green electricity. The combination of these ideal conditions positions Australia to become a “renewable energy superpower.” In order to achieve these goals and for Australia to transition to net-zero emissions, vast amounts of new renewable energy generation will need to be deployed. Much of the suitable and available land for such large-scale renewable development belongs to the Indigenous Estate, including both Aboriginal freehold title and Native Title land. As a result, there could be significant opportunities for Traditional Owners and local First Nations’ communities to participate in and benefit from these developments. However, Australia’s history with the extractive industry has shown that outcomes from land use agreements can be highly variable and do not always deliver their intended benefits. Research shows there is no guarantee that renewable energy developments will deliver beneficial outcomes unless measures are taken to ensure this. In this chapter the authors explore what can be learnt from Australia’s history with the extractive industry, what best practice agreement making looks like, and describe their research methods as they investigate what needs to be done to ensure First Nations’ participation and benefit from large-scale renewable energy developments on Country. No Full Text